Administrative empower in private secondary schools of Al-Qadisiyah governorate - Mhemed, Wedad. M. (Opción, 2019)
The research aimed to identify the level of administrative empowerment in employees of private secondary schools in the governorate of Qadisiyah Iraq via comparative qualitative research methods. Further, t-test and ANOVA test is applied to compare the level of administrative empowerment among different groups. The results show the employees of private secondary schools in Qadisiyah governorate have moderate level of administrative empowerment. In conclusion, the level of empowerment among male and female staff members is not significantly different while level of empowerment is found to be significantly different among employees’ experience.